Implementasi CMMI dalam Sebuah Organisasi Pengembang Software untuk Mencapai Return on Investment (ROI) yang Diinginkan - Arin, Ikrar Adinata (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The main mechanism to achieve a level of maturity in the organization of software developers is always focused, structured and consistent in carrying out work procedures of a quality standard applied. This article offers readers an approach and discourse of using CMMI (Capability Maturity Model Integrated) concept that gives a positive impact on development of organizational business in a software developer. The goals of CMMI are getting the best product quality, increasing productivity, reducing operational costs as well as software development period and increasing customer’s satisfaction. Nevertheless, a leader of the organization should also be able to take important decisions to be consistent with the estimated time of desired return on investment (ROI).